A new species of the Liolaemus elongatus group (Iguania: Liolaemidae)from Neuquén Province, Argentina, with comments on its genital morphology - Ruiz, Maria Soledad (2019)
The Liolaemus elongatus group is a group of lizards that ranges from northwestern Argentina to the southern Patagonian steppe. In this study, we describe a new species of the L. elongatus group. The new taxon is distributed in the vicinity of L. burmeisteri, L. crandalli, L. gununakuna, L. punmahuida and L. tregenzai, and posseses a combination of unique character states and morphological characters that allows its formal description as a new species. The morphological evidence provides strong support that the population under study corresponds to a new taxon. With the description of the new species, the number of members of the L. elongatus group rises to twenty-two, but many populations likely represent undescribed species.